Graft-versus-host disease prophylaxis after transplantation: a network meta-analysis. - Panayiotis D Ziakas; Fainareti N Zervou; Ioannis M Zacharioudakis; Eleftherios Mylonakis (PLoS ONE, 2014)
Background Graft-versus-host Disease (GvHD) prophylaxis after allogeneic hematopoietic stem-cell transplantation (HSCT) is an ongoing effort but relative effects of different policies are not systematically explored. Methods We systematically reviewed 30-year evidence on GvHD prophylaxis and quantified the relative effect of different policies using a network meta-analysis. We searched PubMed and the Cochrane Library for randomized studies on the topic. The primary outcome of interest was grade II-IV acute GvHD over 0 or I (with odds ratio OR <1 denoting benefit). Findings Thirty-three eligible studies that enrolled 3,440 patients (published up to June 2014), provided data on seven immunosuppressive drugs namely cyclosporin A (CsA), methotrexate (MTX), anti-thymocyte globulin (ATG), mycophenolate mofetil (MMF), tacrolimus, sirolimus or corticosteroids and their combinations to calculate 14 direct and 21 indirect effects. The majority of trials (32/33) referred to myeloablative conditioning and sibling transplants (25/33). Tacrolimus/MTX (OR 0.44; 95% 0.27-0.70, number needed to treat to benefit, i.e. to avert a case of II-IV GvHD, NNTB = 5) and ATG/CsA/MTX (OR 0.45; 95%CI 0.26-0.78; NNTB = 5) were superior over CsA/MTX. ATG/CsA/MTX did not differ from tacrolimus/MTX (indirect evidence). Sirolimus-based prophylaxis outperformed CsA/MTX (OR 0.10; 95%CI 0.02-0.49, NNTB = 4) and marginally outperformed tacrolimus/MTX (OR 0.22; 95%CI 0.05-1.11). Add-on corticosteroids had no benefit over CsA/MTX. Conclusions Tacrolimus/MTX and ATG/CsA/MTX were the outperformers over CsA/MTX, but sirolimus-based regimens showed also potential. More randomized data are needed for reduced-intensity conditioning, as well as for MMF and sirolimus-containing regimens.